Vatten som väcker sinnena : förslag för införande av vatten i Alnarps rehabiliteringsträdgård utifrån några miljöpsykologiska teorier - Persson, Karin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Alnarp's Healing Garden is a place for rehabilitation as well as an ongoing multidisciplinary scientific research experiment. The garden is built on research results from the disciplines of Landscape architecture, Environmental Psychology and Garden Therapy. In the garden, people diagnosed with burnout syndromes are being rehabilitated. The participants need safe and calm environments which activate their bodies self healing systems. Theories show that water as an element, per se, increases the observer's preference for an environment. But what is it with water? Why is it calming? How does it affect the experience of an environment? The aim of this project is to design new water features based on literary studies of theories from Environmental Design, Garden Therapy and the participant's needs. The method used for this project is a survey-analyses-design with emphasis on the survey of theories. What is important when experiencing an environment? What are the restorative qualities of water? What are the participant's situations? What demands do they have on their environment? How does the staff work with the garden in Alnarp? Alnarp's Healing Garden is analysed from the theories of environmental psychology, field research, and personal contact with therapist and scientists. Seven new water features are thereafter presented.